Sistem Informasi Pengendalian Persediaan Barang Menggunakan Metode Economic Order Quantity (EOQ) - Erna Astriyani; Desy Apriani; Meri Mayang Sari (UNIVERSITAS RAHARJA, 2020)
The system that is currently running in recording inventory at PT Berlina Tbk Tangerang is considered ineffective and efficient because it still uses paper and the process of inputting and recapping goods data is semi-computerized in Microsoft Excel. which causes problems, namely too much stock of goods so that it increases the load in the warehouse and too little stock of goods which results in an exhaustion of stock in the warehouse. To solve this problem, we need an inventory control information system. The method of analysis uses the EOQ (Economic Order Quantity) method. For the system design process using sublime as the writing language and programming PHP, and XAMPP as localhost, the database uses MySQL. This study aims to design an inventory control system in the HRD department at PT Berlina Tbk Tangerang, and to make it easier for the HRD Department to input and create inventory reports. With this research, it can produce an inventory control system design that is more effective and efficient and can find out the storage costs in the warehouse. From the calculation of the EOQ method, it is found that it is 20% smaller than the previous storage and the total cost of ordering in a year is 2x orders. Thus, it means that there is a very real difference between the inventory policies implemented by the company and the EOQ method.